2021
DOI: 10.1122/8.0000186
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear rheometry of entangled polymeric rings and ring-linear blends

Abstract: We present a comprehensive experimental rheological dataset for purified entangled ring polystyrenes and their blends with linear chains in nonlinear shear and elongation. In particular, data for shear stress growth coefficient, steady-state shear viscosity, and first and second normal stress differences are obtained and discussed as functions of shear rate as well as molecular parameters (molar mass, blend composition and decreasing molar mass of linear component in blend). Over the extended parameter range i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 65 publications
1
44
0
Order By: Relevance
“…They discovered that under start-up shear flow the ring PS exhibits weaker shear thinning with less stress overshoot than the corresponding linear PS. Parisi et al 21,22) recently reported the same trend even for a ring PS with higher M (= 185 kg/mol) (Fig. 2).…”
Section: Rheological Properties Of Ring Polymerssupporting
confidence: 60%
See 1 more Smart Citation
“…They discovered that under start-up shear flow the ring PS exhibits weaker shear thinning with less stress overshoot than the corresponding linear PS. Parisi et al 21,22) recently reported the same trend even for a ring PS with higher M (= 185 kg/mol) (Fig. 2).…”
Section: Rheological Properties Of Ring Polymerssupporting
confidence: 60%
“…Regarding the NLVE of ring/linear polymer blends, Parisi et al 22) examined the nonlinear shear rheology of sym-…”
Section: Rheological Properties Of Ring/ Linear Polymer Blendsmentioning
confidence: 99%
“…Thus, there seem to be two possible regimes of behavior for the viscosity considering the most recent results on polystyrene rings. Either they follow the Rouse-like behavior as suggested by Doi et al's data [131,132,144] or there is a rapid upturn due to entanglement that would be suggested by the data from Kapnistos et al, [129] Pasquino et al, [130] Yan et al, [146] and Parisi et al [145] Because these samples have been made by a ring closure procedure in dilute solution, getting substantially larger pure ring samples seems problematic and newer methods for large ring synthesis are needed. [147] We now return to the problem of the steady state recoverable compliance of the polymer rings and look at the materials that have been fractionated by the LCCC method.…”
Section: Highly Purified Rings: the Lccc Approachmentioning
confidence: 87%
“…Similarly, a rough estimate performed on the published [ 130 ] stress relaxation curves for polyisoprene and for the Kapnistos polystyrene rings seem to have too strong a molecular weight dependence, viz., for the polystyrene rings τMw6.5 while for the polyisoprene rings it seems to vary approximately as τMw4, both of which are much stronger dependences than expected from theory [ 143 ] of τMw2.332.67. Though the above leads to some important questions, the field has gone beyond the results of Kapnistos, et al [ 129 ] and the compilation and new data from Pasquino et al [ 130 ] was also of interest, but newer data from Doi et al [ 131,132,144 ] using LCCC fractionated rings and of Parisi et al [ 145 ] using both LCCC and conventionally fractionated rings suggest that the Kapnistos et al [ 129 ] data may have had a higher linear chain content than originally thought. In Figure 32, we show the polystyrene results from the McKenna et al data, that from Roovers prior to LCCC treatment, the Kapnistos et al data on LCCC treated PS and the Pasquino et al data that included the Kapnistos results as well as results for a sample with a molecular weight of 240,000 g/mol.…”
Section: Dynamics Of Polymer Macrocyclesmentioning
confidence: 99%
See 1 more Smart Citation